Polymethyl methacrylate does not adversely affect the osteogenic potential of human adipose stem cells or primary osteoblasts. Issue 4 (24th October 2019) - Bastidas‐Coral, Angela P.; Bakker, Astrid D.; Kleverlaan, Cornelis J.; Hogervorst, Jolanda M. A.; Klein‐Nulend, Jenneke; Forouzanfar, Tymour
Abstract: Custom‐made polymethyl methacrylate (PMMA) bone cement is used to treat cranial bone defects but whether it is cytotoxic is still unsure. Possible PMMA‐induced adverse effects in vivo affect mesenchymal stem cells and osteoblasts at the implant site. We aimed to investigate whether PMMA affects osteogenic and osteoclast activation potential of human mesenchymal stem cells and/or osteoblasts. Immediately after polymerization, PMMA was added to cultured human adipose stem cells (hASCs) or human osteoblasts (hOBs). Medium lactate dehydrogenase was measured (day 1), metabolic activity, proliferation, osteogenic and osteoclast‐activation marker expression (day 1 and 7), and mineralization (day 14). PMMA did not affect lactate dehydrogenase, KI67 gene expression, or metabolic activity in hASCs and hOBs. PMMA transiently decreased DNA content in hOBs only. PMMA increased COL1 gene expression in hASCs, but decreased RUNX2 in hOBs. PMMA did not affect osteocalcin or alkaline phosphatase (ALP) expression, ALP activity, or mineralization. Only in hOBs, PMMA decreased RANKL/OPG ratio. In conclusion, PMMA is not cytotoxic and does not adversely affect the osteogenic potential of hASCs or hOBs. Moreover, PMMA does not enhance production of osteoclast factors by hASCs and hOBs in vitro. Therefore, PMMA bone cement seems highly suitable to treat patients with cranial bone defects.